Social Participation after Stroke: One-Year Follow-Up of Stroke Survivors in Nigeria. (21st October 2013) - Vincent-Onabajo, Grace O.
Abstract : Background . Stroke may negatively affect social participation in survivors. Aims . This study assessed the pattern of social participation in a sample of Nigerian stroke survivors across the first 12 months after stroke. Methods . Stroke survivors were consecutively recruited while on admission at a tertiary health institution. The London handicap scale was used to assess social participation at 1, 3, 6, 9, and 12 months at the homes of the stroke survivors. Overall and domain-specific patterns of social participation were examined independently and also in relation to initial stroke severity. Results . Overall social participation significantly improved over 12 months (P < 0.0001 ), while significant improvements were observed only in the mobility, physical independence, and work and leisure domains at P equals 0.04, 0.04, and 0.05, respectively. In spite of the improvement in the work and leisure domain, the domain recorded the lowest level of participation. Social participation also differed by initial stroke severity with severe stroke survivors having the lowest level of participation across 12 months after stroke. Conclusions . The poor outcome in the work and leisure domain of social participation and in individuals with initial severe stroke has implications for planning and provision of appropriate long-term stroke rehabilitation.